Population shifts in begomoviruses associated with tomato yellow leaf curl disease in western Mediterranean countries - Granier, Martine; Faize, Mohamed; Passera, Sandie; Urbino, Cica; Peterschmitt, Michel (Peer community journal, 2025)
Tomato yellow leaf curl disease (TYLCD) was reported in western Mediterranean basin since the late 1980s. Based on intensive plant samplings performed in Spain, Italy and Morocco at different periods between the 1990s and 2014, several begomoviruses (family Geminiviridae ) were identified as the cause of TYLCD. They comprise the native Begomovirus solanumflavusardiniaense (Tomato yellow leaf curl Sardinia virus, TYLCSaV), two strains of Begomovirus coheni (Tomato yellow leaf curl virus, TYLCV) introduced from the Middle East, and several types of TYLCV/TYLCSaV recombinants, including the invasive recombinant TYLCV-IS76 in which the genome fragment inherited from TYLCSaV was unusually short. Although parental and recombinant TYLCD-associated begomoviruses were present in each country, country specificities were detected with respect to their relative prevalence, the infection profiles of individual tomato plants, and the recombination patterns of TYLCV/TYLCSaV recombinants. Considering geographic proximities and trade activities between these countries, and the efficient transmission of begomoviruses which are persistently transmitted by the polyphagous and tiny whitefly vector Bemisia tabaci , it was not known if these specificities would be maintained over time. To address this question, 105 tomato samples collected in the three countries between 2015 and 2019 were analysed with PCR tests previously designed to distinguish species, strains and recombinants of TYLCD associated begomoviruses, and with an original PCR test distinguishing emerging resistance-breaking recombinants bearing short TYLCSaV-inherited fragments like TYLCV-IS76 (Srec) from formerly reported recombinants with longer TYLCSaV fragments (Lrec). The results show that country specificities are still present, the most striking being the contrasted geographic distribution of Srec recombinants, with TYLCV-IS76 detected in Morocco but not in Italy, and TYLCV-IS141 and a new Srec recombinant (TYLCV-IMS60-2400) both detected in Italy and not in Morocco. Nevertheless, besides country specificities, a general population shift was revealed regarding TYLCV/TYLCSaV recombinants. Indeed, all the recombinant positive samples, irrespective of their geographic origin, were Srec-positive but Lrec-negative, which suggest that the emergence of Srec recombinants occurred at the expenses of the Lrec recombinants. These results are discussed in relation to the positive selection of Srec recombinants by Ty-1- resistant tomato plants.